Imaging of Brain Tumors. Issue 5 (October 2016) - Baig, Mirza A.; Klein, Joshua P.; Mechtler, Laszlo L.
Abstract : ABSTRACT: Purpose of Review: Neuroimaging is an essential tool for the diagnosis and management of brain tumors. Recent Findings: Advances in neuroimaging have allowed for noninvasive visualization of tumors and have changed how brain tumors are diagnosed and treated. Presurgical planning with the use of functional MRI (fMRI) and diffusion tensor MRI helps to preserve eloquent regions of the brain and fiber tracts, thereby decreasing patients' postsurgical morbidity. With the use of susceptibility-weighted imaging (SWI) filtered phase images, diffusion-weighted studies, and perfusion imaging techniques, deciphering posttreatment effects versus tumor progression can be facilitated. Summary: With recent advancements and novel approaches, various MRI techniques can be used to help diagnose and assist in presurgical planning and posttreatment management of brain tumors.